Social Representations of Women Managers in Private Banking Industry - Poussard, Jale Minibas; Celik, Tutku Seckin; Bingol, Haluk Baran; Akyol, Feyza A. K.; Erkmen, Turhan (INT JOURNAL CONTEMPORARY ECONOMICS & ADMINISTRATIVE SCIENCES, 2023)
In this research, we explored the social representations of women managers in private banking industry in Turkey. Observing the changes and transformations in banking industry and economy through the analysis of data collected in two periods: 2008 (N=220) and 2018 (N=172) from female banking employees, we used the word evocation technique for the analysis of social representations, then generated word cloud visuals to cross-validate our findings. Social representations analysis relies on the Verges method, which takes into account the frequency of finding a word or expression and the rank of appearance, and word cloud visuals were generated to observe the temporal changes and generalized frequencies of evocations over a decade. We observed positive social representations aligning with positive attributes for women managers described in women leadership theories. Positive and negative representations are expressed in different ways by female and male participants. A highlight in our findings was the increase in negative representations for women managers by women participants from 2008 to 2018. This study can provide important insights on the status of gender equality in leadership positions in banking industry in Turkey.
Keywords: Woman Managers; Banking; Social Representations; Management; Gender; GENDER STEREOTYPES; LEADERSHIP; FEMALE; BARRIERS; MEN; Business & Economics